Two new Diastylis (Cumacea: Diastylidae) from Antarctic waters: Diastylis andeepae and D. catalinae - Alberico, Natalia; Mühlenhardt-Siegel, Ute (Zootaxa, 2010)
Two new deep-sea cumaceans, Diastylis andeepae and D. catalinae are described from the Weddell Sea. Diastylis andeepae n. sp. can be distinguished from other members of the genus by a combination of characters including: carapace with small tubercles all over and anterior part with an arched row of teeth extending from each side of the pseudorostrum and disappearing a short distance before reaching the inferior margin of the carapace, ischium of the pereopod 2 with four strong teeth, endopod uropod of two articles. Diastylis catalinae n. sp. is a closely related species to D. richardi Fage 1929 recorded from the Bay of Biscay, however D. catalinae can be easily separated from D. richardi by having: (1) on each side of the anterior part of the carapace several teeth arranged in two non-uniform rows (randomly distributed and with two antero−lateral horns in D. richardi); (2) clearly visible pereonites 1 and 2 in dorsal view (hardly visible in D. richardi); (3) one tooth on each postero−lateral angle of the pereonite 5 (without teeth in D.richardi); and (4) one minute simple seta on article 4 of the antenna 2 (a long setulate seta in D. richardi).